Neurogenic and angiogenic poly(N-acryloylglycine)-co-(acrylamide)-co-(N-acryloyl-glutamate) hydrogel: preconditioning effect under oxidative stress and use in neuroregeneration - Wasnik K.; Gupta P.S.; Singh G.; Maity S.; Patra S.; Pareek D.; Kumar S.; Rai V.; Prakash R.; Acharya A.; Maiti P.; Mukherjee S.; Mastai Y.; Paik P. (My University, 2025)
Traumatic injuries, neurodegenerative diseases and oxidative stress serve as the early biomarkers for neuronal damage and impede angiogenesis and subsequently neuronal growth. Considering this, the present work aimed to develop a poly(N-acryloylglycine)-co-(acrylamide)-co-(N-acryloylglutamate) hydrogel [p(NAG-Ac-NAE)] with angiogenesis/neurogenesis properties. As constituents of this polymer modulate their vital role in biological functions, inhibitory neurotransmitter glycine regulates neuronal homeostasis, and glutamatergic signalling regulates angiogenesis. The p(NAG-Ac-NAE) hydrogel is a highly branched, biodegradable and pH-responsive polymer with a very high swelling behavior of 6188%. The mechanical stability (G′, 2.3-2.7 kPa) of this polymeric hydrogel is commendable in the differentiation of mature neurons. This hydrogel is biocompatible (as tested in HUVEC cells) and helps to proliferate PC12 cells (152.7 ± 13.7%), whereas it is cytotoxic towards aggressive cancers such as glioblastoma (LN229 cells) and triple negative breast cancer (TNBC; MDA-MB-231 cells) and helps to maintain the healthy cytoskeleton framework structure of primary cortical neurons by facilitating the elongation of the axonal pathway. Furthermore, FACS results revealed that the synthesized hydrogel potentiates neurogenesis by inducing the cell cycle (G0/G1) and arresting the sub-G1 phase by limiting apoptosis. Additionally, RT-PCR results revealed that this hydrogel induced an increased level of HIF-1α expression, providing preconditioning effects towards neuronal cells under oxidative stress by scavenging ROS and initiating neurogenic and angiogenic signalling. This hydrogel further exhibits more pro-angiogenic activities by increasing the expression of VEGF isoforms compared to previously reported hydrogels. In conclusion, the newly synthesized p(NAG-Ac-NAE) hydrogel can be one of the potential neuroregenerative materials for vasculogenesis-assisted neurogenic applications and paramount for the management of neurodegenerative diseases. © 2024 The Royal Society of Chemistry.